A Scoping Review of Youth Caregivers: Addressing the Needs of This Growing Population. (17th December 2021) - Doshi, Heena; Chen, Gracie; Bostarr, Norma; Cherry, Debra; Mittelman, Mary; Satyadev, Nihal
Abstract: Generation Z, those who are born in 1997 or thereafter, account for six percent of the estimated 53 million family caregivers in the US – and this percentage is growing, especially given the health impacts of the pandemic. This review focuses on caregiving youth (ages 0-18) and young adult caregivers (ages 18-25) who assist household members who need regular assistance with ADLs and IADLs. This presentation will analyze key trends in the literature of this demographic and identify gaps in research. Our review broadens the knowledge base of how caregiving done by this population impacts brain development, and hence their long term physical, emotional, and mental health. In spite of the significant number of caregiving youth and young adults, current publications on these demographics remain sparse, with most studies being conducted on spousal and adult caregivers. Our group found that the existing literature reviewed the adverse implications on the health and education outcomes for young adult caregivers. This included increased anxiety/depression compared to non-caregivers and for those in post-secondary education, the contribution of caregiving to college incompletion. There are no known studies on this population who have entered the workforce and who also continue their caregiving role. Adequate understanding and characterization of caregiving youth and young adult caregivers will inform better interventions and future policy for them. Support for this demographic, in turn, may improve health outcomes for older adults, who are the majority of those in their care.